HOMA-beta independently predicts survival in patients with advanced cancer on treatment with immune checkpoint inhibitors - Watanabe, Mayu; Eguchi, Jun; Takamoto, Atsushi; Kanzaki, Hiromitsu; Noda, Yohei; Kagawa, Syunsuke; Wada, Jun (Frontiers in Endocrinology, 2024)
Background Although immune checkpoint inhibitors (ICIs) are effective cancer drugs, ICI-induced diabetes is a rare but a life-threatening adverse event for patients. The deleterious action of ICI on pancreatic beta-cell function is a concern. However, the influence of ICI on insulin synthesis and secretion in patients with cancer without diabetes remains unknown. Methods This study included 87 patients diagnosed with advanced cancer. Glucose metabolism markers (HbA1c, HOMA-IR) and indicators of insulin secretory capacity (HOMA-beta, C-peptide) were prospectively evaluated in patients with ICI-treated cancers to determine their association with cancer prognosis. Results Patients with overall survival (OS) ≥ 7 months had substantially higher HOMA-beta levels at baseline (p=0.008) and 1 month after ICI administration (p=0.006) compared to those with OS <7 months. The median OS was significantly longer in patients with HOMA-beta ≥ 64.24 (13 months, 95%CI: 5.849–20.151, 37 events) than in those with HOMA-beta < 64.24 (5 months, 95%CI: 3.280–6.720, 50 events) (p=0.013). Further, the median progression-free survival (PFS) was significantly longer in patients with HOMA-beta ≥ 66.43 (4 months, 95%CI: 3.073–4.927, 33 events) than in those with HOMA-beta < 66.43 (2 months, 95%CI: 1.410–2.590, 54 events) (p=0.025). Additionally, multivariable logistic regression analysis revealed that a HOMA-beta value ≥ 64.24 independently predicted longer OS in ICI-treated patients. Conclusions Pre-ICI HOMA-beta level is linked to longer OS in ICI-treated patients. This connection is significant and shows that insulin secretory capacity may predict ICI efficacy.